IMPLEMENTASI MODEL PENGEMBANGAN SISTEM GDLC DAN ALGORITMA LINEAR CONGRUENTIAL GENERATOR PADA GAME PUZZLE - Rio Andriyat Krisdiawan (FKOM UNIKU, 2018)
Puzzle games, are still in great demand by gamers, because of puzzle solving, mathematical calculations, and even included in educational games. In making the puzzle game, focus on how to make a challenging puzzle game to solve it so that it is not easily guessed / boring with the same pattern when played repeatedly. To answer the question in making the game, researchers conducted research, how to build games with appropriate game development models / methods and how to implement an algorithm in a puzzle game, so that the game becomes more challenging for gamers to solve. In this study, researchers used the GDLC (Game Development Life Cycle) development model, design using UML, and the Implementation of the LCG (Linear Congruental Generator) Algorithm for puzzle random generation in the game. The results of this study are the game development prototype model with GDLC and the implementation of the LCG algorithm for the puzzle generator optimally.Keywords: Games Puzzle, GDLC, UML, LCG